2019
DOI: 10.1051/kmae/2019041
|View full text |Cite
|
Sign up to set email alerts
|

Morphological survey as powerful detection tool of pure and local phenotypes inSalmo truttacomplex

Abstract: The native Mediterranean trout populations in central Italy are at risk of extinction. Hybridization with the alien Atlantic trout represents one of the major threats to the species. The main aim of the research was to test the efficiency of morphological characterization in revealing alien trout introduction, pure lineages and local adaptations, in five watersheds of central Apennines (Italy). Data analysis was carried out for a total of 258 specimens already genetically identified. The results of the multiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 53 publications
2
12
0
Order By: Relevance
“…This was more or less expected as these variables have been repeatedly shown to characterize pigmentation differences between Atlantic or Mediterranean trout in studies previously conducted in France (Poteaux & Berrebi, 1997) and Spain (Aparicio et al, 2005), but, while some spotting traits are important, they are not always found in Italy depending on the local populations analyzed and associated to other not found consistent in our study (e.g. patterns of the adipose fin) (see Lorenzoni et al, 2019). While focusing on few local French populations, results presented in this study reflect former results obtained for these two clades at a broader scale.…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…This was more or less expected as these variables have been repeatedly shown to characterize pigmentation differences between Atlantic or Mediterranean trout in studies previously conducted in France (Poteaux & Berrebi, 1997) and Spain (Aparicio et al, 2005), but, while some spotting traits are important, they are not always found in Italy depending on the local populations analyzed and associated to other not found consistent in our study (e.g. patterns of the adipose fin) (see Lorenzoni et al, 2019). While focusing on few local French populations, results presented in this study reflect former results obtained for these two clades at a broader scale.…”
Section: Discussionsupporting
confidence: 84%
“…Largiadèr & Scholl, 1996; Mezzera, Largiadèr, & Scholl, 1997; Aparicio, García-Berthou, Araguas, Martinez, & Garcia-Marin, 2005; Miyazawa, Okamoto, & Kondo, 2010; Kirczuk & Domagala; 2012, Kocabas, Kutluyer, & Basçinar, 2018), it appears necessary to improve knowledge on the genotype-phenotype association supporting observed pigmentation patterns. Indeed, pigmentation patterns inform on individual origin and use to improve management knowledge, decisions or policies (Ielli & Duchi, 1990; Largiadèr & Scholl, 1996; Poteaux & Berrebi, 1997; Delling, Crivelli, Rubin, & Berrebi, 2000; Aparicio et al, 2005; Kocabas et al, 2011; Marin, Coon, & Fraser, 2017; Duchi, 2018; Lorenzoni et al, 2019). It thus might be relevant to evaluate if loci supporting phenotypic divergence for body patterning reflect genome-wide admixture.…”
Section: Introductionmentioning
confidence: 99%
“…Further, Monet et al (2006) stated that morphological variation caused by genotype was mainly attributable to differences between Mediterranean and Atlantic lineages, making the identification of hybrid trout difficult as they were generally confused with Mediterranean specimens. Similar results for Mediterranean and Atlantic trout lineages and their hybrids were obtained in Italy by Lorenzoni et al (2019). They used a box truss network and spatial arrangement of dots, and determined a significant difference between all three groups.…”
Section: Discussionsupporting
confidence: 60%
“…In addition, Jansson et al (1991), Matthews et al (2000) and Kalayci et al (2018) noted that morphological distinctions of hybrid salmonids from parental species are generally unreliable. However, both Monet et al (2006) and Lorenzoni et al (2019) showed that it is possible to find significant shape distinction between hybrid trout and both parental populations, though they examined parental populations from the Mediterranean and Atlantic lineage, and still hybrids were more similar to the native Mediterranean parental lineage populations.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation